European semi-anthropomorphic phantom for the cross-calibration of peripheral bone densitometers: assessment of precision accuracy and stability. - Pearson, J; Ruegsegger, P; Dequeker, J; Henley, M; Bright, J; Reeve, J; Kalender, W; Felsenberg, D; Laval-Jeantet, A; Adams, J (1994)
A semi-anthropomorphic 'distal radius like' phantom, developed by Kalender and Ruegsegger for use in peripheral bone densitometry using single photon (DPA) dual X-ray (DXA) and quantitative computed tomography (QCT) machines, has been studied with a view to cross-calibrating different types and brands of densitometers in current use. In the context of an EU 'Concerted Action' (second Framework Programme) the phantom was repeatedly measured on six SPA machines, three DXA machines and nine QCT machines (545 measurements). Linear regression equations were derived, individual to each machine, which allowed the derivation of 'standardized densities'. In this way we converted measurements made by machines of the same modality to a common scale of measurements. Two machines (one DXA, one SPA) showed statistically significant instability over time emphasising the need for rigorous quality control in the application of densitometry. In other respects these results provide an encouraging basis for the derivation of standardized normative ranges and the more effective use of peripheral densitometry in future clinical and epidemiological studies.